2018
DOI: 10.1103/physreva.97.063839
|View full text |Cite
|
Sign up to set email alerts
|

Broadband terahertz radiation from two-color mid- and far-infrared laser filaments in air

Abstract: We study terahertz (THz) emission by two-color femtosecond filaments in air using pump wavelengths λ 0 from 0.8 to 10.6 μm. Comprehensive three-dimensional numerical simulations show that tens-of-centimeter long filaments created by a 10.6-μm pump pulse can produce mJ energy yields and GV/m field strengths, while the laser-to-THz conversion efficiency exceeds the percent level. Changing temperature and humidity conditions reveals a surprisingly high stability of the THz spectra against different weather condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(18 citation statements)
references
References 26 publications
2
16
0
Order By: Relevance
“…By taking into account that nonlinear propagation plays a major role in filament-based THz sources, recently we performed theoretical investigations and numerical simulations which predict that twocolor filamentation of mid-infrared laser pulses can be a source of single cycle THz pulses with multi-millijoule energies and extremely high THz conversion efficiencies, which are more than two orders of magnitude higher than for 0.8 μm laser pulses 37,38 . These results were later confirmed numerically by Nguyen et al 39 Additionally, we showed that there is an optimal wavelength for two-color filamentation-induced THz sources: for 3.2 μm laser pulses the THz conversion efficiency reaches its maximum of about 7% 40 . Our theoretical analysis reveled that the extreme efficiency of mid-infrared two-color filamentation for THz generation is caused by a combination of many factors: strong photocurrents due to larger ponderomotive forces, longer and wider plasma channels, negligible walk-off between the fundamental and second harmonic, additional field symmetry breaking by generated high harmonics 37,38 .…”
supporting
confidence: 84%
“…By taking into account that nonlinear propagation plays a major role in filament-based THz sources, recently we performed theoretical investigations and numerical simulations which predict that twocolor filamentation of mid-infrared laser pulses can be a source of single cycle THz pulses with multi-millijoule energies and extremely high THz conversion efficiencies, which are more than two orders of magnitude higher than for 0.8 μm laser pulses 37,38 . These results were later confirmed numerically by Nguyen et al 39 Additionally, we showed that there is an optimal wavelength for two-color filamentation-induced THz sources: for 3.2 μm laser pulses the THz conversion efficiency reaches its maximum of about 7% 40 . Our theoretical analysis reveled that the extreme efficiency of mid-infrared two-color filamentation for THz generation is caused by a combination of many factors: strong photocurrents due to larger ponderomotive forces, longer and wider plasma channels, negligible walk-off between the fundamental and second harmonic, additional field symmetry breaking by generated high harmonics 37,38 .…”
supporting
confidence: 84%
“…Regarding investigated materials, one can note that the studies were not limited to semiconductors only; a special attention gained optical rectification-based THz emission from lithium niobate [20,21] and second-order nonlinear effects for THz generation in different type of organic crystals, like DAST, DSTMS, OH1, HMQ-TMS, and BNA [22][23][24][25][26]. It is worth noting air-plasma-based THz photonics approach when a high intensity femtosecond laser can induce plasma oscillations in air [27,28], which can emit broadband THz radiation [29,30]. However, despite the fact that aforesaid systems contain beautiful physics and can serve as powerful instruments for THz spectroscopy, they are relatively bulky, and they require specific and complicated set-up arrangements.…”
Section: Compact Solutions In Thz Emittersmentioning
confidence: 99%
“…Recent studies [3][4][5][6][7] showed that increasing the pump wavelength enhances the laser-to-THz conversion efficiency which is usually limited to about 10 −4 for near-infrared (IR) pump pulses. However, there is no consensus achieved on the possible gain factors expected when pushing the FH wavelength, λ 0 , from the near-IR to the mid-IR range.…”
mentioning
confidence: 99%